Investigation of stress concentration factor for finite-width orthotropic rectangular plates with a circular opening using three-dimensional finite element model - Bakhshandeh, Kambiz (Strojniški vestnik, 2008)
In this paper, theoretical stress concentration factor for finite-width orthotropic plates with centered circular opening is investigated by use of three-dimensional finite element analysis. In the first part, the finite element (FE) model is validated by comparison analytic equations for infinite orthotropic and isotropic plates. With verified model, the stress concentration factor is calculated for orthotropic rectangular plates with centered circular opening subject to uniform tension. The effect of opening radius to width of plate ratio for various orthotropic plates with different orthotropy ratia is investigated. This study shows the accuracy of analytical method is dependent on orthotropy ratio and a/W ratio. In high opening radius to plate width ratio, the orthotropy ratio has a little effect on stress concentration factor.
Keywords: napetosti; metode končnih elementov; ortotropne plošče